Integrated Momentum and Energy Storage for Mini-Satellites - Ki Bui Ma (The Minerals, Metals and Materials Society, 2002)
Momentum wheels with superconducting bearings can integrate both attitude control and energy storage functions, with attendant savings in the total volume and weight of hardware, and power consumption, all of which are in short supply on mini-satellites. We have built and tested a prototype with a wheel of mass 1.9 kg, diameter 3.25 in, and height 3 in, which can store 3.5 J-sec of angular momentum and 5 kJ of energy when it rotates at an angular speed of 15000 RPM. The energy density of 2.5 kJ/kg achieved is comparable with the lower range for lead-acid batteries. To show that the wheel is energy efficient, we have performed spin down tests and measured the input power required to sustain rotational speed. Results indicate that power consumption, even accounting for the needs of cooling system, is significantly smaller than that for state of the art commercial reaction wheels.